Uso de biomarcadores na avaliação da resposta de larvas e juvenis de pacamã Lophiosilurus alexandri expostos à amônia e ao nitrito em diferentes salinidades e temperaturas - Marcio Jose dos Santos Silva (2017)
The objective of this study was to evaluate the tolerance (LC50-96h) of the larvae of pacamã Lophiosilurus alexandri, with one and seven days of life in different salinities and larvae with twenty days at the temperatures of 25.80± 0.17ºC; 29.07±0.22ºC and 31.53±0.24ºC with 2 of salinity. Juveniles of this same species (one hundred and twenty days of life) were also exposed acutely to increasing concentrations of ammonia and nitrite. Additionally juveniles were submitted to semi-chronic intoxication for eight days and four days detoxification for hematological evaluation. The LC50-96h of the one-day larvae were 0.62 (NS = 0.06) mg.L-1 NH3-N in the treatments without the addition of salt in water and 0.59 (NS = 0.06) mg.L-1 NH3-N in water with 2 of salinity. At seven days of age, the brackish larvae were statistically more tolerant (P <0.05), with LC50-96h estimated to be 1.11 (NS = 0.1) mg.L-1 NH3-N in freshwater and 1.74 (NS = 0.17) mg.L-1 NH3-N in barley medium and 3.06 (NS = 0.3) mg.L-1 NH3-N in 20 day animals. Nitrite was significantly (P <0.05) more toxic for 1-day larvae maintained in freshwater, LC50-96h = 170.39 (NS = 17.0) mg.L-1 NO2--N than in the salinized environment = LC50 -96h = 967.98 (NS = 96.98) mg.L-1 NO2--N. In the larvae of seven days of life, LC50-96h were estimated to be 234.05 mg.L-1 NO2--N and 495.97 mg.L-1 NO2--N, for fresh and brackish water, respectively. At the three temperatures tested (26, 29 and 32ºC) with NH3 and NO2- in the brackish environment, there were no significant differences (P> 0.05) between the treatments, and the LC50-96h were estimated at 3.06 (NS = 0.3); 2.63 (NS = 0.26) and 3.66 (NS = 0.37) mg.L-1 NH3-N, respectively. The estimated LC50-96h for nitrite was 342.70 (NS = 34.3); 347.49 (NS = 34.7) and 388.03 (NS = 38.8) mg.L-1 NO2--N. The juveniles of 120 days responded with CL50-96h = 3.66 mg.L-1 NH3-N and 5.86 mg.L-1 NO2--N, respectively. Histopathological analysis of larvae found that gills were developing and tissue differentiation. The most frequent lesion was respiratory epithelial detachment. The results indicate that with age and in a brackish environment, the pacamã larva increased tolerance to ammonia intoxication. Salinity increased larval tolerance to nitrite, but decreased with age development. Acute exposure to ammonia has elevated the enzymes transaminases, glucose and urea. The urea concentration remained high in the sub chronic and detoxification tests. The most observed lesions were respiratory epithelial detachment, hyperemia and necrosis. Exposure to nitrite also caused epithelial detachment and aneurysm. Vaccination and edema of hepatocytes were effects caused by both pollutants. It is concluded that the tolerance of pacamã to nitrogen compounds increases with increasing age and larval size, and in salinized environment at 2 . In this study we also verified that the toxicity did not differ in the three temperatures tested. The juveniles present moderate tolerance to the nitrogen compounds and the recovery period presented a corrective response to the subchronic damages caused by these pollutants.